Social inclusion, care and belonging of children with spina bifida: perspectives from Uganda - Bannink, Femke (Afrika Focus, 2017)
This study presents a situation analysis on daily functioning, caregiving, and inclusion of children with spina bifida in Uganda. 139 children with spina bifida and their families from 4 regions in Uganda participated in this study. Findings show how a complex play of cultural values, globalization and access to biomedical care determines knowledge, and negative attitudes about, and perception of children with spina bifida. Families and private non for profit organisations are the main providers of care of the children. Children with spina bfida had a more negative perception of themselves, were less likely to be in school, and had lower cognitive outcome compared to their siblings. Daily functioning and social inclusion were affected by motor function, incontinence, lack of support for caregivers, low household income, limited resources and knowledge of inclusive teaching, bullying, and inaccessibility of public transport, roads, and buildings. Positive experiences of belonging were found at family and household level and were closely related to the ‘ubuntu’ concept. When a child belongs, the child has a chance to live, to participate, to become, to be included. To facilitate inclusion, families need to be supported, and negative attitudes and behaviour of community members, teachers, and health workers need to be addressed. Key words: disability, inclusion, spina bifida, Uganda, Africa